Relative Contributions of Strength, Anthropometric, and Body Composition Characteristics to Estimated Propulsive Force in Young Male Swimmers. Issue 6 (June 2015) - Cochrane, Kristen C.; Housh, Terry J.; Smith, Cory M.; Hill, Ethan C.; Jenkins, Nathaniel D.M.; Johnson, Glen O.; Housh, Dona J.; Schmidt, Richard J.; Cramer, Joel T.
Abstract : Abstract: Cochrane, KC, Housh, TJ, Smith, CM, Hill, EC, Jenkins, NDM, Johnson, GO, Housh, DJ, Schmidt, RJ, and Cramer, JT. Relative contributions of strength, anthropometric, and body composition characteristics to estimated propulsive force in young male swimmers. J Strength Cond Res 29(6): 1473–1479, 2015—The purpose of this study was to determine the relative contributions of isokinetic forearm flexion (FLX) and extension (EXT) peak torque (PT) at 180°·s −1, height (HT), percent body fat (%BF), and fat-free mass (FFM) to the prediction of estimated propulsive force (EPF) and which of these variables should be a focus of training in young male swimmers. Thirty young male swimmers (mean age ± SD = 12.4 ± 2.7 years) volunteered for this study. The subjects were members of local swimming clubs who competed in the front crawl. The swimmers were measured for FLX and EXT PT at 180°·s −1, HT, body mass (BM), arm muscle area (AMA), arm circumference, triceps skinfold, %BF, and FFM. Arm muscle area was used to calculate EPF. Zero-order correlations and stepwise multiple regression analyses were used to examine the relationships among variables and the relative contributions of FLX, EXT, HT, %BF, and FFM to the prediction of EPF. Forearm flexion PT at 180°·s −1, EXT, BM, HT, FFM, AMA, and EPF were significantly intercorrelated ( r = 0.83–1.00). In addition, 4 variables contributed significantly to the prediction of EPF (standardized regression coefficients = FFM [1.00], FLX [0.92], EXT [−0.62], and HT [−0.35]). Percent body fat did not contribute to any of the stepwise models. These findings suggested that age-related increases in HT and FFM, as well as training for increases in FLX and EXT strength may improve propulsive force and swimming performance in young male swimmers.